Access the future of education : social sciences [electronic resource] (Rice University, 1999)
Quoted from the homepage: Our open source textbooks are written by professional content developers who are experts in their fields. All textbooks meet standard scope and sequence requirements, making them seamlessly adaptable into existing courses. OpenStax textbooks undergo a rigorous peer review process. View the list of contributors when you click on each book.